Design And Analysis Of a Multi-channel Optical Fibre Lan Based On Modified Csma/cd Protocol - Ahmad Anas, Siti Barirah (2002)
Nowadays, optical communication is widely employed by telecommunication providers in the whole world due to its ability to support high bit rate applications. The urge to provide end-to-end fibre connectivity arises to overcome the bottleneck problem that occurs when packets are transmitted on the slower speed medium such as copper. In optical transmission, bandwidth utilisation can be improved further by using multiple wavelengths or channels in a single fibre. This thesis discusses the implementation of multiple wavelengths technique for Local Area Network (LAN) environment. It proposes a new Ethernet-based protocol that uses multiple wavelengths for transmission, which runs on a single fibre. Ethernet/IEEE 802.3 is chosen because of its widespread employment in today's network and the ability of extending the transmission rate up to gigabit transmission. Even though light does not collide with each other, receiver contention might occur if more than one signal arrives at the receiver at the same time. Therefore, some arbitration mechanism is needed to synchronise the transmission and the tuning time of the respective transmitter and receiver. The proposed design is based on the physical bus topology with n number of connected nodes and m number of operating wavelengths. All nodes are able to listen to all wavelengths. A fast control unit is used, which is responsible for packet scheduling. The packets are scheduled based on a pre-computed time. Both transmitter and receiver will be asked to tune to the· allocated wavelength. The transmitter can start transmitting and the receiver will start tuning at a specified time. Control packets are used for handshaking purposes. The main operation is placed at the control unit so that no added complexity is experienced by the receiver. Thus, this technique further reduces the cost. A suitable range of channels is obtained from the result. The network performance is evaluated against several design parameters by comparing the performance of each channel. The result shows a significant improvement whereby the throughput and efficiency are increased and average delay is minimised compared to the conventional system.